2015
DOI: 10.1111/jmcb.12231
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Transfers and Fiscal Sustainability

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 72 publications
0
23
1
10
Order By: Relevance
“…Regarding the economic level of a region we have found no significant influence of GDP on the financial sustainability, although previous studies showed a positive relationship with the public revenues and could help local governments to reduce the debt [50][51][52][53]. This result could be due to an increase in GDP does not always imply an increase in the national taxes that local governments participate.…”
Section: Rq 2 -Does the Company's Concentration Affect The Financial contrasting
confidence: 44%
See 1 more Smart Citation
“…Regarding the economic level of a region we have found no significant influence of GDP on the financial sustainability, although previous studies showed a positive relationship with the public revenues and could help local governments to reduce the debt [50][51][52][53]. This result could be due to an increase in GDP does not always imply an increase in the national taxes that local governments participate.…”
Section: Rq 2 -Does the Company's Concentration Affect The Financial contrasting
confidence: 44%
“…This partnership would promote public revenues [50] and decreased debt [51], which would cause a positive effect on the finances of local governments. In the same vein, Ghosh et al [52] and Potrafke and Reischmann [53] concluded that the economic level of a region is a key to analyze the financial viability of it, to the extent that it affects the ability of local governments to provide public services element and thus boosting the sustainability of regional development. It is, therefore, interesting to analyze the effect of changing the economic level of a territory on the financial sustainability of Local Governments.…”
Section: Research Questionsmentioning
confidence: 99%
“…In contrast, those of the German case are negative and significant at the 1% degree of economic growth in the long run, although the rules are not stringent in the short run, as stated in Poterba (1996) and Potrafke and Reischmann (2015).…”
Section: Panel Cointegrating Vector Estimationsmentioning
confidence: 80%
“…As documented in Potrafke and Reischmann (2015), although intergovernmental fiscal transfers are implemented to fund the budgets of state and local governments in the federal systems of both the United States and Germany, a key difference in fiscal transfer systems exists between the two countries. In the United States, the transfer payments are only vertical, and the federal government transfers to the states.…”
Section: Panel Cointegration Analysis Of Wagner's Law For Us and Gementioning
confidence: 99%
See 1 more Smart Citation